A polycrystalline diamond cutter and a method of making the same

CN122875754APending Publication Date: 2026-10-09NANJING JINRUI LIFENG HARD MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611181632.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

但传统聚晶金刚石采用纯钴作为粘结相,高温下钴易催化金刚石石墨化,700℃以上即发生失效,且无法阻隔碳元素向铁族金属、钛合金工件扩散,长期以来无法稳定加工钛合金、淬硬钢等难加工材料

Benefits of technology

[0029]1.本发明通过预合金成分设计与烧结过程元素偏聚控制,原位形成富钴核-碳化物壳的核壳结构粘结相,有效解决了传统钴粘结相的固有缺陷。本发明采用成分为钴80-85wt%、钛8-12wt%、铬7-10wt%的气雾化预合金粉作为粘结相,在高温高压烧结过程中,钛、铬元素自发向金刚石晶粒表面偏聚,与金刚石表面碳元素原位反应生成连续碳化钛、碳化三铬包覆层,内部保留富钴相,形成核壳结构粘结相。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875754A_ABST
    Figure CN122875754A_ABST
Patent Text Reader

Abstract

The application discloses a polycrystalline diamond cutter and a preparation method thereof, and relates to the technical field of cutting tools.The cutter is provided with a tungsten carbide-cobalt hard alloy as a base body, and a three-gradient-structure polycrystalline diamond composite layer is combined on the surface of the base body; the binder phase in the layer is a core-shell structure of a cobalt-rich core and a carbide shell which is generated in-situ in high-temperature and high-pressure sintering; a composition-continuous transition layer is arranged between the base body and the polycrystalline diamond layer; the cutting edge is strengthened by ion implantation; and a hydrophilic-hydrophobic composite wetting texture is prepared, so that the problems of poor thermal stability, easy delamination of the interface and easy collapse of the traditional polycrystalline diamond are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cutting tool technology, specifically a polycrystalline diamond cutting tool and its preparation method. Background Technology

[0002] Polycrystalline diamond (PCD) tools are widely used in high-speed cutting of non-ferrous metals and composite materials due to their high hardness and excellent wear resistance. They are core tools for machining difficult-to-machine materials in the aerospace and automotive manufacturing fields. However, traditional PCD tools use pure cobalt as a binder phase. At high temperatures, cobalt easily catalyzes the graphitization of diamond, leading to failure above 700°C. Furthermore, PCD tools cannot prevent the diffusion of carbon elements into ferrous metals and titanium alloys, making it difficult to reliably machine difficult-to-machine materials such as titanium alloys and hardened steel for a long time.

[0003] Meanwhile, traditional polycrystalline diamonds are mostly homogeneous in composition and structure, unable to simultaneously achieve high surface hardness and high core toughness. The mismatch in thermal expansion coefficients with the cemented carbide matrix easily leads to interfacial delamination failure, resulting in micro-chipping at the cutting edge. Furthermore, the single-surface microtexture cannot directionally transport lubricant, causing severe tool sticking when cutting titanium alloys. Existing improvement solutions mostly employ a cobalt-free binder phase or a single particle size gradient structure. The former requires ultra-high pressure sintering, resulting in extremely high equipment costs and hindering industrial-scale implementation. The latter only adjusts the diamond particle size distribution, failing to fundamentally solve the high-temperature failure of the binder phase and the interfacial stress problem, thus offering limited overall performance improvement. Summary of the Invention

[0004] The present invention aims to provide a polycrystalline diamond cutting tool and its preparation method to solve the related technical problems existing in the prior art.

[0005] To achieve the above-mentioned objectives, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing a polycrystalline diamond tool includes the following steps: S1: Pretreatment of cemented carbide substrate: The surface of the tungsten carbide-cobalt cemented carbide substrate is subjected to laser etching, acid etching to remove cobalt, washing, and drying to obtain a pretreated substrate;

[0007] Furthermore, the cobalt content of the tungsten carbide-cobalt cemented carbide matrix is ​​10 wt%.

[0008] S2: Powder assembly: In the pyrophyllite high-temperature and high-pressure sintering mold, the pretreated matrix, transition layer powder, polycrystalline diamond powder near the matrix, intermediate layer polycrystalline diamond powder, and polycrystalline diamond powder near the cutting edge are placed from bottom to top, and pre-pressed layer by layer to obtain the blank to be sintered.

[0009] Furthermore, the transition layer powder is composed of diamond micro powder and carbide-cobalt powder; the polycrystalline diamond powder near the matrix, the intermediate polycrystalline diamond powder, and the polycrystalline diamond powder near the cutting edge are composed of diamond micro powder and cobalt-titanium-chromium pre-alloy powder.

[0010] Furthermore, the cobalt content of the carbide-cobalt powder is 10 wt%;

[0011] Furthermore, the cobalt-titanium-chromium pre-alloyed powder has a composition of 80-85 wt% cobalt, 8-12 wt% titanium, and 7-10 wt% chromium, with a particle size of 1-3 μm;

[0012] S3: High temperature and high pressure sintering: The blank to be sintered is placed in a high temperature and high pressure equipment for sintering to obtain polycrystalline diamond composite sheet;

[0013] Furthermore, the sintering pressure is 4.5-5 GPa, the temperature is 1250-1350℃, and the time is 5-10 min;

[0014] S4: Post-processing: The polycrystalline diamond composite sheet is sequentially subjected to wire electrical discharge cutting, edge strengthening, ultrasonic-assisted brazing, and tribochemical polishing to obtain a polycrystalline diamond tool.

[0015] Furthermore, the laser etching employs a regular hexagonal micro-pit array with a pit diameter of 25-35 μm, a depth of 18-22 μm, and a center-to-center spacing of 50 μm; the acid etching for cobalt removal uses a nitric acid-hydrochloric acid mixed solution with a volume ratio of 1:3, and acid etching is performed at room temperature for 1-2 minutes.

[0016] Furthermore, the polycrystalline diamond powder near the matrix side is composed of 85-88 wt% diamond micro powder and 12-15 wt% cobalt-titanium-chromium pre-alloyed powder, and the diamond micro powder has a particle size of 8-10 μm.

[0017] Furthermore, the intermediate layer polycrystalline diamond powder is composed of 90-92 wt% diamond micro powder and 8-10 wt% cobalt-titanium-chromium pre-alloyed powder, and the diamond micro powder has a particle size of 2-4 μm.

[0018] Furthermore, the polycrystalline diamond powder near the cutting edge is composed of 94-96 wt% diamond micro powder and 4-6 wt% cobalt-titanium-chromium pre-alloyed powder, and the diamond micro powder has a particle size of 0.3-0.8 μm.

[0019] Furthermore, the transition layer powder is composed of 40-60 wt% diamond micro powder and 40-60 wt% carbide-cobalt powder, with the diamond micro powder having a particle size of 5-7 μm.

[0020] Furthermore, the thickness of the transition layer powder is 15-25 μm, the thickness of the polycrystalline diamond powder near the substrate is 640-800 μm, the thickness of the intermediate layer polycrystalline diamond powder is 480-640 μm, and the thickness of the polycrystalline diamond powder near the cutting edge is 160-320 μm; the layer-by-layer pre-compression pressure is 10-15 MPa.

[0021] Furthermore, the specific steps of the edge strengthening treatment are as follows: nitrogen and boron composite particles are implanted into the 95-105μm range of the edge; wherein the implantation depth is 200-300nm, the implantation energy is 60-80keV for nitrogen particles and 30-50keV for boron particles, and the beam current density is 0.5-1.5mA / cm. 2 .

[0022] Furthermore, the post-processing also includes the following steps: sequentially performing electrical discharge wire cutting, edge strengthening, preparation of a hydrophilic-reactive composite wettability texture, ultrasonic-assisted brazing, and tribochemical polishing on the polycrystalline diamond composite sheet to obtain a polycrystalline diamond tool.

[0023] Furthermore, the specific steps for preparing the affinity-reluctance composite wettability texture are as follows: Step 1: In the area 100-150μm away from the main cutting edge, pulsed fiber laser processing is used to obtain a micro-nano texture parallel to the main cutting edge;

[0024] Step 2: Immerse the cutting tool from Step 1 in a 0.8-1wt% fluoroalkylsilane solution for 24 hours, remove it, and heat it to 140-145℃ for 100-120 minutes to cure it; thus obtaining a micro-nano hydrophobic texture parallel to the main cutting edge.

[0025] Step 3: In the micro-nano hydrophobic textured area of ​​the tool in Step 2, a hydrophilic microgroove perpendicular to the main cutting edge is processed using a pulsed fiber laser. Then, the fluoroalkyl silane hydrophobic layer at the bottom of the hydrophilic microgroove is removed by laser ablation. Finally, a mixed solid lubricant is filled into the hydrophilic microgroove.

[0026] Furthermore, in step one, the pulsed fiber laser parameters are: pulse energy 0.25 mJ, scanning speed 80 mm / s, 2 scans, scanning line spacing 30-35 μm, and texture depth 9-11 μm; in step three, the pulsed fiber laser parameters are: pulse energy 0.7 mJ, scanning speed 200 mm / s, 1 scan, microgroove width 55-65 μm, and microgroove depth 9-11 μm; the solid lubricant is a mixture of hexagonal boron nitride and molybdenum disulfide in a mass ratio of 1:1.

[0027] Furthermore, the ultrasonic-assisted brazing uses silver-copper-titanium active brazing filler metal, the brazing temperature is 680-720℃, and the holding time is 20-40s.

[0028] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0029] 1. This invention effectively solves the inherent defects of traditional cobalt binder phases by designing the pre-alloying composition and controlling element segregation during the sintering process to form a core-shell structure binder phase with a cobalt-rich core and carbide shell in situ. This invention uses gas-atomized pre-alloying powder with a composition of 80-85 wt% cobalt, 8-12 wt% titanium, and 7-10 wt% chromium as the binder phase. During high-temperature and high-pressure sintering, titanium and chromium spontaneously segregate to the surface of diamond grains, reacting in situ with carbon elements on the diamond surface to generate a continuous titanium carbide and chromium tricarbide coating layer, while retaining the cobalt-rich phase internally.

[0030] This structure completely blocks direct contact between cobalt and diamond, suppressing the high-temperature failure problem of cobalt-catalyzed diamond graphitization. On the other hand, it strengthens the bonding of diamond grain boundaries, reducing the diamond particle pull-out rate during cutting. At the same time, the continuous carbide layer can act as a high-temperature diffusion barrier, blocking the diffusion of carbon elements into titanium alloys and iron group metal workpieces during cutting, solving the industry pain point that traditional polycrystalline diamond cannot stably process steel and titanium alloys.

[0031] 2. This invention achieves a smooth transition in performance from the cemented carbide matrix side to the cutting edge side through continuous gradient adjustment. This results in a coarse-grained, highly bonded phase layer near the matrix providing excellent impact toughness, while a fine-grained, low-bonded phase layer near the cutting edge provides high hardness and a sharp cutting edge. The intermediate layer achieves a smooth transition in performance, avoiding abrupt performance changes and stress concentration caused by layered powdering. A transition layer is set between the matrix and the polycrystalline diamond layer, with a continuous transition in the coefficient of thermal expansion from the matrix side to the polycrystalline diamond side. This reduces residual stress at the interface and allows for deflection during crack propagation, further improving fracture toughness.

[0032] 3. This invention further enhances the interfacial bonding performance through micro-nano dual-scale texture pretreatment of the substrate: the hexagonal laser micro-pit array on the substrate bonding surface forms a micron-level mechanical interlocking, and the porous layer formed by acid etching and cobalt removal forms a nano-level pinning effect during sintering, which works synergistically with the transition layer to further improve the interfacial bonding strength.

[0033] 4. The present invention introduces residual compressive stress and generates a nano-hard phase by ion implantation of nitrogen-boron composite into the cutting edge, thereby inhibiting the initiation of microcracks and improving the cutting edge's resistance to chipping. The prepared hydrophilic-reactive composite wettability texture enables the directional transport of micro-lubricant through surface tension difference. Combined with the hexagonal boron nitride / molybdenum disulfide solid lubricant filled in the groove, it effectively reduces the average coefficient of friction and avoids thermal damage and graphitization of polycrystalline diamond caused by high-temperature brazing. Through a multi-process synergistic post-treatment system, the cutting performance and service life of the tool are further improved. Attached Figure Description

[0034] Figure 1 This is a schematic diagram of the affinity-repulsion composite wettability texture structure of a polycrystalline diamond cutting tool according to the present invention. Detailed Implementation

[0035] The technical solutions in the embodiments of the present invention are described in detail and completely below. It should be understood that the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other equivalent embodiments obtained by those skilled in the art based on the embodiments disclosed in this invention without creative effort are within the protection scope of this invention.

[0036] In the following examples, the diamond micro powder is type Ib synthetic diamond micro powder with a nitrogen content ≤100ppm; the tungsten carbide-cobalt cemented carbide matrix has a cobalt content of 10wt%; the cobalt-titanium-chromium pre-alloy powder is prepared by vacuum atomization, with an average particle size of 1-3μm and an oxygen content ≤500ppm; the silver-copper-titanium active solder composition is 68wt% silver, 27wt% copper, and 5wt% titanium; the remaining raw materials are commercially available.

[0037] Example 1: A method for preparing a polycrystalline diamond tool, comprising the following steps: S1: Pretreatment of cemented carbide substrate: The surface of the tungsten carbide-cobalt cemented carbide substrate is subjected to laser etching, acid etching to remove cobalt, washing, and drying to obtain a pretreated substrate;

[0038] The laser etching employs a hexagonal micro-pit array, with each pit having a diameter of 30 μm, a depth of 20 μm, and a center-to-center spacing of 50 μm. The acid etching for cobalt removal uses a 1:3 volume ratio nitric acid-hydrochloric acid mixture, etched at room temperature for 1.5 min.

[0039] S2: Powder assembly: In the pyrophyllite high-temperature and high-pressure sintering mold, the pretreated matrix, transition layer powder, polycrystalline diamond powder near the matrix, intermediate layer polycrystalline diamond powder, and polycrystalline diamond powder near the cutting edge are placed from bottom to top, and pre-pressed layer by layer to obtain the blank to be sintered.

[0040] The polycrystalline diamond powder near the matrix side is composed of 86.5 wt% diamond micro powder and 13.5 wt% cobalt-titanium-chromium pre-alloyed powder, and the diamond micro powder has a particle size of 9 μm.

[0041] The intermediate layer polycrystalline diamond powder is composed of 91 wt% diamond micro powder and 9 wt% cobalt-titanium-chromium pre-alloyed powder, and the diamond micro powder has a particle size of 3 μm.

[0042] The polycrystalline diamond powder near the cutting edge is composed of 95 wt% diamond micro powder and 5 wt% cobalt-titanium-chromium pre-alloyed powder, with the diamond micro powder having a particle size of 0.5 μm.

[0043] The transition layer powder is composed of 50 wt% diamond micro powder and 50 wt% carbide-cobalt powder, with the diamond micro powder having a particle size of 6 μm.

[0044] The cobalt-titanium-chromium pre-alloyed powder has a composition of 82wt% cobalt, 10wt% titanium, and 8wt% chromium, with a particle size of 2μm.

[0045] The transition layer powder thickness is 20 μm, the polycrystalline diamond powder thickness near the substrate side is 720 μm, the intermediate layer polycrystalline diamond powder thickness is 560 μm, and the polycrystalline diamond powder thickness near the cutting edge side is 240 μm; the layer-by-layer pre-compression pressure is 12 MPa.

[0046] S3: High temperature and high pressure sintering: The blank to be sintered is placed in a high temperature and high pressure equipment for sintering to obtain polycrystalline diamond composite sheet;

[0047] The sintering pressure was 5 GPa, the temperature was 1300℃, and the time was 8 min.

[0048] S4: Post-processing: The polycrystalline diamond composite sheet is sequentially subjected to wire electrical discharge cutting, edge strengthening, ultrasonic-assisted brazing, and tribochemical polishing to obtain a polycrystalline diamond tool.

[0049] The specific steps of the edge strengthening treatment are as follows: nitrogen and boron composite particles are implanted into a 100μm range of the edge; wherein the implantation depth is 250nm, the implantation energy is 70keV for nitrogen particles and 40keV for boron particles, and the beam current density is 1mA / cm. 2 .

[0050] The ultrasonic-assisted brazing uses silver-copper-titanium active brazing filler metal, the brazing temperature is 720℃, and the holding time is 20s.

[0051] Example 2: A method for preparing a polycrystalline diamond tool, comprising the following steps: S1: Pretreatment of cemented carbide substrate: The surface of the tungsten carbide-cobalt cemented carbide substrate is subjected to laser etching, acid etching to remove cobalt, washing, and drying to obtain a pretreated substrate;

[0052] The laser etching employs a hexagonal micropit array with a pit diameter of 25 μm, a depth of 18 μm, and a center-to-center spacing of 50 μm. The acid etching for cobalt removal uses a 1:3 volume ratio nitric acid-hydrochloric acid mixture, etched at room temperature for 1 min.

[0053] S2: Powder assembly: In the pyrophyllite high-temperature and high-pressure sintering mold, the pretreated matrix, transition layer powder, polycrystalline diamond powder near the matrix, intermediate layer polycrystalline diamond powder, and polycrystalline diamond powder near the cutting edge are placed from bottom to top, and pre-pressed layer by layer to obtain the blank to be sintered.

[0054] The polycrystalline diamond powder near the matrix side is composed of 88wt% diamond micro powder and 12wt% cobalt-titanium-chromium pre-alloyed powder, with the diamond micro powder having a particle size of 8μm.

[0055] The intermediate layer polycrystalline diamond powder is composed of 92 wt% diamond micro powder and 8 wt% cobalt-titanium-chromium pre-alloyed powder, and the diamond micro powder has a particle size of 2 μm.

[0056] The polycrystalline diamond powder near the cutting edge is composed of 96 wt% diamond micro powder and 4 wt% cobalt-titanium-chromium pre-alloyed powder, with the diamond micro powder having a particle size of 0.3 μm.

[0057] The transition layer powder is composed of 40wt% diamond micro powder and 60wt% carbide-cobalt powder, and the diamond micro powder has a particle size of 5μm.

[0058] The cobalt-titanium-chromium pre-alloyed powder has a composition of 85wt% cobalt, 8wt% titanium, and 7wt% chromium, with a particle size of 2μm.

[0059] The transition layer powder thickness is 15 μm, the polycrystalline diamond powder thickness near the substrate side is 640 μm, the intermediate layer polycrystalline diamond powder thickness is 480 μm, and the polycrystalline diamond powder thickness near the cutting edge side is 160 μm; the layer-by-layer pre-compression pressure is 10 MPa.

[0060] S3: High temperature and high pressure sintering: The blank to be sintered is placed in a high temperature and high pressure equipment for sintering to obtain polycrystalline diamond composite sheet;

[0061] The sintering pressure was 4.5 GPa, the temperature was 1250℃, and the time was 10 min.

[0062] S4: Post-processing: The polycrystalline diamond composite sheet is sequentially subjected to wire electrical discharge cutting, edge strengthening, ultrasonic-assisted brazing, and tribochemical polishing to obtain a polycrystalline diamond tool.

[0063] The specific steps of the edge strengthening treatment are as follows: nitrogen and boron composite particles are implanted into a 95μm range of the edge; wherein the implantation depth is 200nm, the implantation energy is 60keV for nitrogen particles and 30keV for boron particles, and the beam current density is 0.5mA / cm. 2 .

[0064] The ultrasonic-assisted brazing uses silver-copper-titanium active brazing filler metal, the brazing temperature is 720℃, and the holding time is 20s.

[0065] Example 3: A method for preparing a polycrystalline diamond tool, comprising the following steps: S1: Pretreatment of cemented carbide substrate: The surface of the tungsten carbide-cobalt cemented carbide substrate is subjected to laser etching, acid etching to remove cobalt, washing, and drying to obtain a pretreated substrate;

[0066] The laser etching employs a hexagonal micropit array with a pit diameter of 35 μm, a depth of 22 μm, and a center-to-center spacing of 50 μm. The acid etching for cobalt removal uses a 1:3 volume ratio nitric acid-hydrochloric acid mixture solution, etched at room temperature for 2 minutes.

[0067] S2: Powder assembly: In the pyrophyllite high-temperature and high-pressure sintering mold, the pretreated matrix, transition layer powder, polycrystalline diamond powder near the matrix, intermediate layer polycrystalline diamond powder, and polycrystalline diamond powder near the cutting edge are placed from bottom to top, and pre-pressed layer by layer to obtain the blank to be sintered.

[0068] The polycrystalline diamond powder near the matrix side is composed of 85wt% diamond micro powder and 15wt% cobalt-titanium-chromium pre-alloyed powder, with the diamond micro powder having a particle size of 10μm.

[0069] The intermediate layer polycrystalline diamond powder is composed of 90 wt% diamond micro powder and 10 wt% cobalt-titanium-chromium pre-alloyed powder, with the diamond micro powder having a particle size of 4 μm.

[0070] The polycrystalline diamond powder near the cutting edge is composed of 94 wt% diamond micro powder and 6 wt% cobalt-titanium-chromium pre-alloyed powder, with the diamond micro powder having a particle size of 0.8 μm.

[0071] The transition layer powder is composed of 60 wt% diamond micro powder and 40 wt% carbide-cobalt powder, with the diamond micro powder having a particle size of 7 μm.

[0072] The cobalt-titanium-chromium pre-alloyed powder has a composition of 85wt% cobalt, 8wt% titanium, and 7wt% chromium, with a particle size of 2μm.

[0073] The transition layer powder thickness is 25 μm, the polycrystalline diamond powder thickness near the substrate side is 800 μm, the intermediate layer polycrystalline diamond powder thickness is 640 μm, and the polycrystalline diamond powder thickness near the cutting edge side is 320 μm; the layer-by-layer pre-compression pressure is 15 MPa.

[0074] S3: High temperature and high pressure sintering: The blank to be sintered is placed in a high temperature and high pressure equipment for sintering to obtain polycrystalline diamond composite sheet;

[0075] The sintering pressure was 5 GPa, the temperature was 1350℃, and the time was 5 min.

[0076] S4: Post-processing: The polycrystalline diamond composite sheet is sequentially subjected to wire electrical discharge cutting, edge strengthening, ultrasonic-assisted brazing, and tribochemical polishing to obtain a polycrystalline diamond tool.

[0077] The specific steps of the edge strengthening treatment are as follows: nitrogen and boron composite particles are implanted into a 105μm range of the edge; wherein the implantation depth is 200nm, the implantation energy is 80keV for nitrogen particles and 50keV for boron particles, and the beam current density is 1.5mA / cm. 2 .

[0078] The ultrasonic-assisted brazing uses silver-copper-titanium active brazing filler metal, the brazing temperature is 720℃, and the holding time is 20s.

[0079] Example 4: A method for preparing a polycrystalline diamond tool, comprising the following steps: S1: Pretreatment of cemented carbide substrate: The surface of the tungsten carbide-cobalt cemented carbide substrate is subjected to laser etching, acid etching to remove cobalt, washing, and drying to obtain a pretreated substrate;

[0080] The laser etching employs a hexagonal micro-pit array, with each pit having a diameter of 30 μm, a depth of 20 μm, and a center-to-center spacing of 50 μm. The acid etching for cobalt removal uses a 1:3 volume ratio nitric acid-hydrochloric acid mixture, etched at room temperature for 1.5 min.

[0081] S2: Powder assembly: In the pyrophyllite high-temperature and high-pressure sintering mold, the pretreated matrix, transition layer powder, polycrystalline diamond powder near the matrix, intermediate layer polycrystalline diamond powder, and polycrystalline diamond powder near the cutting edge are placed from bottom to top, and pre-pressed layer by layer to obtain the blank to be sintered.

[0082] The polycrystalline diamond powder near the matrix side is composed of 86.5 wt% diamond micro powder and 13.5 wt% cobalt-titanium-chromium pre-alloyed powder, and the diamond micro powder has a particle size of 9 μm.

[0083] The intermediate layer polycrystalline diamond powder is composed of 91 wt% diamond micro powder and 9 wt% cobalt-titanium-chromium pre-alloyed powder, and the diamond micro powder has a particle size of 3 μm.

[0084] The polycrystalline diamond powder near the cutting edge is composed of 95 wt% diamond micro powder and 5 wt% cobalt-titanium-chromium pre-alloyed powder, with the diamond micro powder having a particle size of 0.5 μm.

[0085] The transition layer powder is composed of 50 wt% diamond micro powder and 50 wt% carbide-cobalt powder, with the diamond micro powder having a particle size of 6 μm.

[0086] The cobalt-titanium-chromium pre-alloyed powder has a composition of 82wt% cobalt, 10wt% titanium, and 8wt% chromium, with a particle size of 2μm.

[0087] The transition layer powder thickness is 20 μm, the polycrystalline diamond powder thickness near the substrate side is 720 μm, the intermediate layer polycrystalline diamond powder thickness is 560 μm, and the polycrystalline diamond powder thickness near the cutting edge side is 240 μm; the layer-by-layer pre-compression pressure is 12 MPa.

[0088] S3: High temperature and high pressure sintering: The blank to be sintered is placed in a high temperature and high pressure equipment for sintering to obtain polycrystalline diamond composite sheet;

[0089] The sintering pressure was 5 GPa, the temperature was 1300℃, and the time was 8 min.

[0090] S4: Post-processing: The polycrystalline diamond composite sheet is sequentially subjected to wire electrical discharge cutting, edge strengthening, preparation of affinity-repulsion composite wettability texture, ultrasonic-assisted brazing, and tribochemical polishing to obtain a polycrystalline diamond tool.

[0091] The specific steps of the edge strengthening treatment are as follows: nitrogen and boron composite particles are implanted into a 100μm range of the edge; wherein the implantation depth is 250nm, the implantation energy is 70keV for nitrogen particles and 40keV for boron particles, and the beam current density is 1mA / cm. 2 .

[0092] The specific steps for preparing the affinity-reluctance composite wettability texture are as follows: Step 1: In the area 120μm away from the main cutting edge, pulsed fiber laser processing is used to obtain a micro-nano texture parallel to the main cutting edge;

[0093] Step 2: Immerse the cutting tool from Step 1 in a 0.8wt% fluoroalkylsilane solution for 24 hours, remove it, and heat it to 140℃ for 120 minutes to cure; thus obtaining a micro-nano hydrophobic texture parallel to the main cutting edge.

[0094] Step 3: In the micro-nano hydrophobic textured area of ​​the tool from Step 2, a hydrophilic microgroove perpendicular to the main cutting edge is machined using a pulsed fiber laser. Then, the % fluoroalkyl silane hydrophobic layer at the bottom of the hydrophilic microgroove is removed by laser ablation. Finally, a mixed solid lubricant is filled into the hydrophilic microgroove.

[0095] In step one, the pulsed fiber laser parameters are: pulse energy 0.25 mJ, scanning speed 80 mm / s, 2 scans, scanning line spacing 30 μm, and texture depth 9 μm; in step three, the pulsed fiber laser parameters are: pulse energy 0.7 mJ, scanning speed 200 mm / s, 1 scan, microgroove width 55 μm, and microgroove depth 9 μm; the solid lubricant is a mixture of hexagonal boron nitride and molybdenum disulfide in a mass ratio of 1:1.

[0096] The ultrasonic-assisted brazing uses silver-copper-titanium active brazing filler metal, the brazing temperature is 720℃, and the holding time is 20s.

[0097] Comparative Example 1: A method for preparing a polycrystalline diamond cutting tool, comprising the following steps: S1: Powder assembly: In a pyrophyllite high-temperature and high-pressure sintering mold, a tungsten carbide-cobalt cemented carbide matrix, a transition layer powder, a polycrystalline diamond powder near the matrix, an intermediate layer of polycrystalline diamond powder, and a polycrystalline diamond powder near the cutting edge are placed sequentially from bottom to top, and pre-pressed layer by layer to obtain a blank to be sintered;

[0098] The polycrystalline diamond powder near the matrix side is composed of 86.5 wt% diamond micro powder and 13.5 wt% cobalt-titanium-chromium pre-alloyed powder, and the diamond micro powder has a particle size of 9 μm.

[0099] The intermediate layer polycrystalline diamond powder is composed of 91 wt% diamond micro powder and 9 wt% cobalt-titanium-chromium pre-alloyed powder, and the diamond micro powder has a particle size of 3 μm.

[0100] The polycrystalline diamond powder near the cutting edge is composed of 95 wt% diamond micro powder and 5 wt% cobalt-titanium-chromium pre-alloyed powder, with the diamond micro powder having a particle size of 0.5 μm.

[0101] The transition layer powder is composed of 50 wt% diamond micro powder and 50 wt% carbide-cobalt powder, with the diamond micro powder having a particle size of 6 μm.

[0102] The cobalt-titanium-chromium pre-alloyed powder has a composition of 82wt% cobalt, 10wt% titanium, and 8wt% chromium, with a particle size of 2μm.

[0103] The transition layer powder thickness is 20 μm, the polycrystalline diamond powder thickness near the substrate side is 720 μm, the intermediate layer polycrystalline diamond powder thickness is 560 μm, and the polycrystalline diamond powder thickness near the cutting edge side is 240 μm; the layer-by-layer pre-compression pressure is 12 MPa.

[0104] S2: High temperature and high pressure sintering: The blank to be sintered is placed in a high temperature and high pressure equipment for sintering to obtain polycrystalline diamond composite sheet;

[0105] The sintering pressure was 5 GPa, the temperature was 1300℃, and the time was 8 min.

[0106] S3: Post-processing: The polycrystalline diamond composite sheet is sequentially subjected to wire electrical discharge cutting, edge strengthening, ultrasonic-assisted brazing, and tribochemical polishing to obtain a polycrystalline diamond tool.

[0107] The specific steps of the edge strengthening treatment are as follows: nitrogen and boron composite particles are implanted into a 100μm range of the edge; wherein the implantation depth is 250nm, the implantation energy is 70keV for nitrogen particles and 40keV for boron particles, and the beam current density is 1mA / cm. 2 .

[0108] The ultrasonic-assisted brazing uses silver-copper-titanium active brazing filler metal, the brazing temperature is 720℃, and the holding time is 20s.

[0109] Comparative Example 2: A method for preparing a polycrystalline diamond tool, comprising the following steps: S1: Pretreatment of cemented carbide substrate: The surface of a tungsten carbide-cobalt cemented carbide substrate is subjected to laser etching, acid etching to remove cobalt, washing, and drying to obtain a pretreated substrate;

[0110] The laser etching employs a hexagonal micro-pit array, with each pit having a diameter of 30 μm, a depth of 20 μm, and a center-to-center spacing of 50 μm. The acid etching for cobalt removal uses a 1:3 volume ratio nitric acid-hydrochloric acid mixture, etched at room temperature for 1.5 min.

[0111] S2: Powder assembly: In the pyrophyllite high-temperature and high-pressure sintering mold, the pretreated matrix, polycrystalline diamond powder near the matrix, polycrystalline diamond powder in the middle layer, and polycrystalline diamond powder near the cutting edge are placed from bottom to top, and pre-pressed layer by layer to obtain the blank to be sintered.

[0112] The polycrystalline diamond powder near the matrix side is composed of 86.5 wt% diamond micro powder and 13.5 wt% cobalt-titanium-chromium pre-alloyed powder, and the diamond micro powder has a particle size of 9 μm.

[0113] The intermediate layer polycrystalline diamond powder is composed of 91 wt% diamond micro powder and 9 wt% cobalt-titanium-chromium pre-alloyed powder, and the diamond micro powder has a particle size of 3 μm.

[0114] The polycrystalline diamond powder near the cutting edge is composed of 95 wt% diamond micro powder and 5 wt% cobalt-titanium-chromium pre-alloyed powder, with the diamond micro powder having a particle size of 0.5 μm.

[0115] The cobalt-titanium-chromium pre-alloyed powder has a composition of 82wt% cobalt, 10wt% titanium, and 8wt% chromium, with a particle size of 2μm.

[0116] The thickness of the polycrystalline diamond powder near the matrix is ​​720 μm, the thickness of the intermediate layer is 560 μm, and the thickness of the polycrystalline diamond powder near the cutting edge is 240 μm; the layer-by-layer pre-compression pressure is 12 MPa.

[0117] S3: High temperature and high pressure sintering: The blank to be sintered is placed in a high temperature and high pressure equipment for sintering to obtain polycrystalline diamond composite sheet;

[0118] The sintering pressure was 5 GPa, the temperature was 1300℃, and the time was 8 min.

[0119] S4: Post-processing: The polycrystalline diamond composite sheet is sequentially subjected to wire electrical discharge cutting, edge strengthening, ultrasonic-assisted brazing, and tribochemical polishing to obtain a polycrystalline diamond tool.

[0120] The specific steps of the edge strengthening treatment are as follows: nitrogen and boron composite particles are implanted into a 100μm range of the edge; wherein the implantation depth is 250nm, the implantation energy is 70keV for nitrogen particles and 40keV for boron particles, and the beam current density is 1mA / cm. 2 .

[0121] The ultrasonic-assisted brazing uses silver-copper-titanium active brazing filler metal, the brazing temperature is 720℃, and the holding time is 20s.

[0122] Comparative Example 3: A method for preparing a polycrystalline diamond tool, comprising the following steps: S1: Pretreatment of cemented carbide substrate: The surface of a tungsten carbide-cobalt cemented carbide substrate is subjected to laser etching, acid etching to remove cobalt, washing, and drying to obtain a pretreated substrate;

[0123] The laser etching employs a hexagonal micro-pit array, with each pit having a diameter of 30 μm, a depth of 20 μm, and a center-to-center spacing of 50 μm. The acid etching for cobalt removal uses a 1:3 volume ratio nitric acid-hydrochloric acid mixture, etched at room temperature for 1.5 min.

[0124] S2: Powder assembly: In the pyrophyllite high temperature and high pressure sintering mold, the pretreated matrix, the transition layer powder, and the polycrystalline diamond powder near the matrix are placed from bottom to top, and pre-pressed layer by layer to obtain the blank to be sintered.

[0125] The polycrystalline diamond powder near the matrix side is composed of 86.5 wt% diamond micro powder and 13.5 wt% cobalt-titanium-chromium pre-alloyed powder, and the diamond micro powder has a particle size of 9 μm.

[0126] The transition layer powder is composed of 50 wt% diamond micro powder and 50 wt% carbide-cobalt powder, with the diamond micro powder having a particle size of 6 μm.

[0127] The cobalt-titanium-chromium pre-alloyed powder has a composition of 82wt% cobalt, 10wt% titanium, and 8wt% chromium, with a particle size of 2μm.

[0128] The transition layer powder thickness is 20 μm, and the polycrystalline diamond powder thickness near the matrix side is 1600 μm; the layer-by-layer pre-compression pressure is 12 MPa.

[0129] S3: High temperature and high pressure sintering: The blank to be sintered is placed in a high temperature and high pressure equipment for sintering to obtain polycrystalline diamond composite sheet;

[0130] The sintering pressure was 5 GPa, the temperature was 1300℃, and the time was 8 min.

[0131] S4: Post-processing: The polycrystalline diamond composite sheet is sequentially subjected to wire electrical discharge cutting, edge strengthening, ultrasonic-assisted brazing, and tribochemical polishing to obtain a polycrystalline diamond tool.

[0132] The specific steps of the edge strengthening treatment are as follows: nitrogen and boron composite particles are implanted into a 100μm range of the edge; wherein the implantation depth is 250nm, the implantation energy is 70keV for nitrogen particles and 40keV for boron particles, and the beam current density is 1mA / cm. 2 .

[0133] The ultrasonic-assisted brazing uses silver-copper-titanium active brazing filler metal, the brazing temperature is 720℃, and the holding time is 20s.

[0134] Performance testing: Thermal stability test: The temperature was increased at a rate of 10℃ / min in air atmosphere using a synchronous thermal analyzer, and the temperature corresponding to a mass loss of 0.5% was taken as the initial oxidation temperature;

[0135] Interfacial shear strength test: A universal testing machine with a dedicated interfacial shear fixture was used to test the interfacial shear strength between the polycrystalline diamond layer and the matrix at a loading rate of 0.5 mm / min.

[0136] Mechanical property testing: Under a load of 10mN, the microhardness of the cutting edge was tested using a nanoindenter; the transverse fracture strength was tested using the three-point bending method; after intermittent cutting of HT250 gray cast iron for 30 minutes, the maximum micro-chipping width of the cutting edge was statistically analyzed by scanning electron microscopy to characterize the impact resistance.

[0137] Tribological performance testing: ball-disc friction test, with the mating part being a TC4 titanium alloy ball, load of 5N, linear velocity of 0.5m / s, and the average coefficient of friction was tested;

[0138] Cutting performance test: Turning TC4 titanium alloy bar, cutting speed 120m / min, feed 0.15mm / r, depth of cut 0.3mm, micro-lubrication, with the wear of the flank face VB=0.3mm as the dulling standard, and the cutting length is recorded as the tool life.

[0139] The performance test results are shown in Table 1 below.

[0140] Table 1 Performance Test Data of Polycrystalline Diamond Tools

[0141]

[0142] Conclusion: This invention achieves a significant improvement in the overall performance of polycrystalline diamond tools through multi-scale synergistic strengthening.

[0143] It will be apparent to those skilled in the art that the present invention is not limited to the specific details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit and core features of the invention. Therefore, the above embodiments should be considered exemplary rather than restrictive in any respect. The scope of protection of the present invention is defined by the appended claims, not by the foregoing description, and is therefore intended to encompass all variations in the meaning and scope of the equivalents of the claims within the scope of the present invention.

Claims

1. A method for preparing a polycrystalline diamond cutting tool, characterized in that: Includes the following steps: S1: Pretreatment of cemented carbide substrate: The surface of the tungsten carbide-cobalt cemented carbide substrate is subjected to laser etching, acid etching to remove cobalt, washing and drying to obtain the pretreated substrate; S2: Powder assembly: In a high-temperature and high-pressure sintering mold, the pre-treated matrix, transition layer powder, polycrystalline diamond powder near the matrix, intermediate layer polycrystalline diamond powder, and polycrystalline diamond powder near the cutting edge are placed from bottom to top, and pre-pressed layer by layer to obtain the blank to be sintered. The transition layer powder is composed of diamond micro powder and carbide-cobalt powder; the polycrystalline diamond powder near the matrix, the intermediate polycrystalline diamond powder, and the polycrystalline diamond powder near the cutting edge are composed of diamond micro powder and cobalt-titanium-chromium pre-alloy powder. S3: High temperature and high pressure sintering: The blank to be sintered is placed in a high temperature and high pressure equipment for sintering to obtain polycrystalline diamond composite sheet; S4: Post-processing: The polycrystalline diamond composite sheet is sequentially subjected to wire electrical discharge cutting, edge strengthening, ultrasonic-assisted brazing, and tribochemical polishing to obtain a polycrystalline diamond tool.

2. The method for preparing a polycrystalline diamond cutting tool according to claim 1, characterized in that: The laser etching employs a regular hexagonal micro-pit array with a pit diameter of 25-35 μm, a depth of 18-22 μm, and a center-to-center spacing of 50 μm. The acid etching for cobalt removal uses a nitric acid-hydrochloric acid mixed solution with a volume ratio of 1:3, and is performed at room temperature for 1-2 minutes.

3. The method for preparing a polycrystalline diamond cutting tool according to claim 1, characterized in that: The polycrystalline diamond powder near the matrix side is composed of 85-88 wt% diamond micro powder and 12-15 wt% cobalt-titanium-chromium pre-alloyed powder, with the diamond micro powder having a particle size of 8-10 μm. The intermediate layer polycrystalline diamond powder is composed of 90-92 wt% diamond micro powder and 8-10 wt% cobalt-titanium-chromium pre-alloyed powder, with the diamond micro powder having a particle size of 2-4 μm. The polycrystalline diamond powder near the cutting edge is composed of 94-96 wt% diamond micro powder and 4-6 wt% cobalt-titanium-chromium pre-alloyed powder, with the diamond micro powder having a particle size of 0.3-0.8 μm. The transition layer powder is composed of 40-60 wt% diamond micro powder and 40-60 wt% carbide-cobalt powder, with the diamond micro powder having a particle size of 5-7 μm.

4. The method for preparing a polycrystalline diamond cutting tool according to claim 1, characterized in that: The thickness of the transition layer powder is 15-25 μm, the thickness of the polycrystalline diamond powder near the substrate is 640-800 μm, the thickness of the intermediate layer polycrystalline diamond powder is 480-640 μm, and the thickness of the polycrystalline diamond powder near the cutting edge is 160-320 μm; the layer-by-layer pre-compression pressure is 10-15 MPa.

5. The method for preparing a polycrystalline diamond cutting tool according to claim 1, characterized in that: The specific steps of the edge strengthening treatment are as follows: nitrogen and boron composite particles are implanted into the 95-105μm range of the edge; wherein the implantation depth is 200-300nm, the implantation energy is 60-80keV for nitrogen particles and 30-50keV for boron particles, and the beam current density is 0.5-1.5mA / cm. 2 .

6. The method for preparing a polycrystalline diamond cutting tool according to claim 1, characterized in that: The post-processing also includes the following steps: sequentially performing electrical discharge wire cutting, edge strengthening, preparation of affinity-repulsion composite wettability texture, ultrasonic-assisted brazing, and tribochemical polishing on the polycrystalline diamond composite sheet to obtain a polycrystalline diamond tool.

7. The method for preparing a polycrystalline diamond cutting tool according to claim 6, characterized in that: The specific steps for preparing the affinity-reluctance composite wettability texture are as follows: Step 1: In the area 100-150μm away from the main cutting edge, pulsed fiber laser processing is used to obtain a micro-nano texture parallel to the main cutting edge. Step 2: Immerse the cutting tool from Step 1 in a 0.8-1wt% fluoroalkylsilane solution for 24 hours, remove it, and heat it to 140-145℃ for 100-120 minutes to cure it; thus obtaining a micro-nano hydrophobic texture parallel to the main cutting edge. Step 3: In the micro-nano hydrophobic textured area of ​​the tool from Step 2, a hydrophilic microgroove perpendicular to the main cutting edge is machined using a pulsed fiber laser. Then, the fluoroalkyl silane hydrophobic layer at the bottom of the hydrophilic microgroove is removed by laser ablation. Finally, a mixed solid lubricant is filled into the hydrophilic microgroove.

8. The method for preparing a polycrystalline diamond cutting tool according to claim 7, characterized in that: In step one, the pulsed fiber laser parameters are: pulse energy 0.25 mJ, scanning speed 80 mm / s, 2 scans, scanning line spacing 30-35 μm, and texture depth 9-11 μm; in step three, the pulsed fiber laser parameters are: pulse energy 0.7 mJ, scanning speed 200 mm / s, 1 scan, microgroove width 55-65 μm, and microgroove depth 9-11 μm; the solid lubricant is a mixture of hexagonal boron nitride and molybdenum disulfide in a mass ratio of 1:

1.

9. A polycrystalline diamond tool prepared by the method for preparing a polycrystalline diamond tool according to any one of claims 1-8.